Citraan Dalam Buku Puisi Tantrum Karya Adhan Akram - Anis Anis; Albertus Purwaka; Indra Perdana; Alifiah Nurachmana; Jumadi Jumadi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The purpose of this research is to describe the visual imagery, auditory imagery, tactile imagery, olfactory imagery, gustatory imagery, and kinetic imagery found in the poetry book Tantrum by Adhan Akram. This research is qualitative descriptive in nature. The data source for this study is the poetry book Tantrum by Adhan Akram, consisting of 65 poems. The data consists of types of imagery ranging from visual imagery, auditory imagery, tactile imagery, olfactory imagery, gustatory imagery, and kinetic imagery found in the poems of the poetry book Tantrum by Adhan Akram, with the data taking the form of words, phrases, clauses, or sentences found within the lines of poetry related to imagery in the poetry book Tantrum by Adhan Akram. Data collection techniques are carried out through reading and note-taking. Data analysis is conducted using qualitative research methods. Based on the analysis results, it can be concluded that in the poetry book Tantrum by Adhan Akram, the author employs six types of imagery in the poems, namely visual imagery, auditory imagery, tactile imagery, olfactory imagery, gustatory imagery, and kinetic imagery. The data containing imagery in the poetry book Tantrum by Adhan Akram, classified according to its types, amounted to 127 instances. The most abundant data is found in visual imagery, with 55 instances, while the least data is found in gustatory imagery, with only 4 instances.